Poslovodni organi u ostvarivanju unutarnje kontrole u cestovnom prometu - Javorović, Božidar (Promet - Traffic&Transportation, 2012)
An ever increasing growth of traffic and its importance in the economic and overall social life of nations and countries on one side and respective increase of fatalities and material loss (damage to property} on the other set an indispensable requirement of increased care and concern over the safety and quality of traffic. Safety is to the best of interests of any individual and all road users and all parties having something to do with this activity. As an important factor of business efficiency and success road traffic safety becomes more and more an important part of preoccupations of managerial bodies of transport and other companies. As the internal control makes an aspect of protection and safety activity having a special role in materialization of traffic safety in transport operations, it is to the best interests and a responsibility of managerial bodies to act in this area on a permanent basis and continuously pay adequate attention to the issue of safety. It is important for the quality of road traffic/transport activities and success in business operations.